Novel dalbavancin-PLLA implant coating prevents hematogenous Staphylococcus aureus infection in a minimally invasive mouse tail vein model - Kloss, Marlen; Moerke, Caroline; Woitschach, Franziska; Wulf, Katharina; Illner, Sabine; Schulz, Steffen; Pauker, Viktoria I.; Riedel, Katharina; Grabow, Niels; Ince, Hüseyin; Reisinger, Emil C.; Sombetzki, Martina (Frontiers in Bioengineering and Biotechnology, 2022)
Infective/bacterial endocarditis is a rare but life-threatening disease with a hospital mortality rate of 22.7% and a 1-year mortality rate of 40%. Therefore, continued research efforts to develop efficient anti-infective implant materials are of the utmost importance. Equally important is the development of test systems that allow the performance of new materials to be comprehensively evaluated. In this study, a novel antibacterial coating based on dalbavancin was tested in comparison to rifampicin/minocycline, and the suitability of a recently developed mouse tail vein model for testing the implant coatings was validated. Small polymeric stent grafts coated with a poly-L-lactic acid (PLLA) layer and incorporated antibiotics were colonized with Staphylococcus (S.) aureus before implantation into the tail vein of mice. The main assessment criteria were the hematogenous spread of the bacteria and the local tissue reaction to the contaminated implant. For this purpose, colony-forming units (CFU) in the blood, spleen and kidneys were determined. Tail cross sections were prepared for histological analysis, and plasma cytokine levels and expression values of inflammation-associated genes were examined. Both antibiotic coatings performed excellently, preventing the onset of infection. The present study expands the range of available methods for testing the anti-infectivity of cardiovascular implants, and the spectrum of agents for effective surface coating.